Use of Diction in Monster Inc Movie - Antonio Constantino Soares; Rika Purnama Sari; I Gusti Ayu Agung Wira Premagitari (Austronesian: Journal of Language Science & Literature, 2022)
The research aims to describe the selection and use of vocabulary, the use of word morphological and syntactical aspects and the use of figurative language, especially the speech of the Monster Inc movie’s actors. This study used the descriptive qualitative method. The data was taken from the movie of Monster Inc. The data was analyzed based on Miles’ theory, namely data condensation, data display and drawing a conclusion. The results show that non-standard words, informal, showing stronger impressions, and emphasizing certain information tend to use in the movie. Morphologically aspect, words are used in the form of reduplication of words and phrases to emphasize what is being conveyed. Also, it was found that there is no affixation, reduplication, or compounding. Furthermore, syntactically aspect, most sentences are delivered in interrogative sentences, command clauses, complete sentences, exclamations, incomplete sentences, informative sentences, complete informational sentences, ungrammatical sentences, and complex sentences. The last figurative language used in several scenes is idiomatic phrases, metaphors, personification, and similes.